Electrode assembly

By designing the convex and concave structures on the positive electrode sheet of the lithium-ion battery and adjusting the adhesive force on the separator, the problems of poor electrolyte infiltration and gas accumulation during long circulation are solved, and the service life and safety of the battery are improved performance.

CN119480901AActive Publication Date: 2025-02-18ZHUHAI COSMX BATTERY CO LTD

Patent Information

Application Number
CN202411742310.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-02-18
Estimated Expiration
2044-11-29

AI Technical Summary

Technical Problem

During the long cycle of lithium-ion batteries, the interface abnormalities caused by electrochemical performance decay, poor electrolyte infiltration, and gas accumulation in high-temperature environments affect the safety performance and service life of the battery.

Method used

An electrode assembly is designed, the positive electrode sheet has a convex and concave structure, and the diaphragm has different adhesive forces on different surfaces of the positive electrode sheet to build a gas discharge path to improve the wetting ability of the electrolyte and the gas discharge efficiency.

Benefits of technology

Through the design of the convex and concave parts, the storage space of the electrolyte is increased, its wetting ability is improved, and the service life of the battery is extended. At the same time, by adjusting the adhesive force of the diaphragm, gas discharge is optimized and gas accumulation is reduced The resulting interface abnormality improves the safety performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119480901A_ABST
    Figure CN119480901A_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of batteries, and provides an electrode assembly and a battery wherein the electrode assembly comprises: a positive plate having a first surface and a second surface opposite to each other in the thickness direction, the first surface having a plurality of protrusions, and the second surface having a plurality of recesses corresponding to the protrusions and recessed toward the protrusions; the diaphragms are respectively adhered to the first surface and the second surface; wherein the adhesive force between the first surface and the diaphragm is N1, the adhesive force between the second surface and the diaphragm is N2, and N1 and N2 meet the relational expression of N1gt; n2; according to the embodiment of the invention, the battery performance can be optimized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to an electrode assembly. Background Art

[0002] Lithium-ion batteries (LIBs) currently dominate the portable electronic device battery market due to their high specific energy density, wide temperature range and long cycle life; lithium iron phosphate materials and ternary materials are widely used in the market due to their respective characteristics.

[0003] However, during the long-term use of the above materials, the electrochemical performance is seriously attenuated, the power performance is not satisfactory, and the capacity retention rate is getting worse and worse. On the one hand, the interlayer extrusion of the battery cell is relatively serious, and the electrolyte is difficult to enter, resulting in poor electrolyte infiltration;

[0004] On the other hand, under high-temperature formation or high-temperature cycle testing conditions, the battery may produce gases (such as hydrogen). If these gases cannot be discharged in time, the pressure inside the battery will increase and may lead to poor interface bonding between the electrode and the diaphragm. Poor interface bonding will cause the transmission of lithium ions to be blocked, leading to lithium precipitation, seriously affecting the safety performance of the battery. Summary of the invention

[0005] The present application provides an electrode assembly that can solve the problems of poor electrolyte infiltration of the electrode assembly and interface abnormalities caused by high-temperature gas production.

[0006] The present application provides an electrode assembly, comprising: a positive electrode sheet, a negative electrode sheet, and a separator located between the positive electrode sheet and the negative electrode sheet;

[0007] The positive electrode sheet has a first surface and a second surface opposite to each other in the thickness direction, the first surface has a plurality of convex portions, and the second surface has a plurality of concave portions respectively corresponding to the convex portions and concave toward the convex portions;

[0008] The diaphragm includes a first diaphragm and a second diaphragm; the first diaphragm is bonded to the first surface; the second diaphragm is bonded to the second surface; the first diaphragm is bonded beyond the head end of the positive electrode sheet and the second diaphragm is bonded beyond the head end of the positive electrode sheet;

[0009] The adhesion between the first surface and the diaphragm is N1, the adhesion between the second surface and the diaphragm is N2, and N1 and N2 satisfy the relationship:

[0010] N1>N2.

[0011] According to the electrode assembly described in the first aspect of the present application, by forming convex and concave portions on the two surfaces of the positive electrode sheet, the surface of the positive electrode sheet is uneven, so that when the battery cell expands, the convex portion can effectively support the diaphragm, and prevent the diaphragm or the positive electrode sheet from being deformed by the expansion stress of the negative electrode sheet. At the same time, a space for accommodating electrolyte is formed between the convex portion of the positive electrode sheet and the diaphragm, thereby increasing the storage space of the electrolyte, improving the infiltration capacity of the electrolyte in this area, and avoiding abnormal situations such as insufficient electrolyte and poor infiltration between the positive electrode and the diaphragm. Furthermore, the positive electrode sheet forms a concave portion, thereby expanding the storage space of the electrolyte, further enhancing the wettability of the electrolyte, and improving the cycle performance and service life of the electrode assembly.

[0012] In addition, by setting the bonding force between the surface where the convex portion is located and the diaphragm to be greater than the bonding force between the surface where the concave portion is located and the diaphragm, a gas discharge path is constructed, so that during the high-temperature formation or high-temperature expansion process, the gas generated by the electrochemical reaction is preferentially discharged from the place where the bonding force is weaker (such as between each concave portion and the diaphragm). It can be understood that the diaphragm itself has a certain air permeability, and by forming convex portions and concave portions on the positive electrode sheet, the distance between the positive electrode sheet and the diaphragm is expanded. At the same time, the bonding force between the surface where the concave portion is located and the diaphragm is smaller, which means that the bonding area between the surface where the concave portion is located and the diaphragm is relatively small, and there are more gaps between the surface where the concave portion is located and the diaphragm, so that the internal pressure of the battery can be released in time, reducing the possibility of bubbles formed due to gas accumulation inside the battery cell, and further reducing the possibility of purple spots caused by abnormal bonding interface between the positive electrode sheet and the diaphragm or the diaphragm and the negative electrode sheet in the central area of ​​the electrode assembly due to gas production, so that the positive electrode sheet and the diaphragm maintain good interface contact, which is conducive to more uniform current density distribution on the positive electrode sheet and the diaphragm during the cycle, avoiding uneven deposition of lithium metal and the resulting formation of lithium dendrites.

[0013] Moreover, timely discharge of gas through the weaker bonding points can also play a heat dissipation role to a certain extent, which is beneficial to maintaining the temperature of the positive electrode during the cycle, so that the heat inside the battery cell is evenly dispersed, thereby creating a stable reaction environment inside the battery cell and preventing further occurrence of side reactions, thereby improving the cycle performance of the battery and extending the battery life.

[0014] According to an embodiment of the present invention, N1=(1.01-2)N2.

[0015] According to an embodiment of the present invention, the surface of the convex portion in contact with the diaphragm is a curved surface.

[0016] According to an embodiment of the present invention, the convex portion is spherical or quasi-spherical, the radius of the convex portion is R1, and the radius of the concave portion is R2; R1 and R2 satisfy the relationship: R1 / R2=1.01-2.

[0017] According to one embodiment of the present invention, R1=0.5mm~8mm; and / or R2=0.5mm~8mm; and / or, the height of the protrusion from the endpoint of the second surface to the surface of the positive electrode sheet is h1; h1=3μm~40μm.

[0018] According to one embodiment of the present invention, a plurality of the protrusions are distributed at intervals, and the positive electrode sheet includes a straight portion between two adjacent protrusions; the spacing between the centers of two adjacent protrusions is L1, and the length of the straight portion between two adjacent protrusions is L2, and L1 and L2 satisfy the relationship: L1 / L2=1.05~10.

[0019] According to one embodiment of the present invention, L1 = 3 mm to 10 mm; and / or L2 = 0.5 mm to 8 mm.

[0020] According to one embodiment of the present invention, the area of ​​the convex portion is Q1, the area of ​​the concave portion is Q2, and Q1 and Q2 satisfy the relationship: Q1 / Q2=1.02~1.21; and / or, the projection area of ​​the convex portion in the thickness direction of the positive electrode sheet is S1, the projection area of ​​the concave portion in the thickness direction of the positive electrode sheet is S2, and S1 and S2 satisfy the relationship: S1 / S2=1.02~1.21.

[0021] According to one embodiment of the present invention, the number of the protrusions within the unit area of ​​the positive electrode sheet is N, and N satisfies the relationship: 2≤N≤25, and / or the total projection area of ​​each of the protrusions within the unit area in the thickness direction of the positive electrode sheet is S3, and the proportion of S3 within the unit area satisfies the relationship: 0.2≤S3≤0.8.

[0022] According to one embodiment of the present invention, the area on the positive electrode sheet where the convexities are concentrated is a convexity area, the total area of ​​the convexity area is S11, the total area of ​​the positive electrode sheet is S, and S11 and S satisfy the relationship: 0.02≤S11 / S≤0.85.

[0023] According to one embodiment of the present invention, the spacing between the protrusion area and the two end edges of the positive electrode sheet in the length direction is K, and K=10mm~100mm; and / or the spacing between the protrusion area and any end edge of the positive electrode sheet in the width direction is M, and M=5mm~30mm.

[0024] According to one embodiment of the present invention, the positive electrode sheet, the separator and the negative electrode sheet are stacked and wound to form a core structure, and the electrode assembly includes a main body area and an arc area; the height of the convex portion located in the arc area is smaller than the height of the convex portion located in the main body area.

[0025] According to one embodiment of the present invention, the separator includes: a base film, the base film includes a multi-layer microporous film; a ceramic layer, the ceramic layer is coated on the base film, and the ceramic layer and the positive electrode sheet are arranged opposite to each other.

[0026] According to one embodiment of the present invention, the metal element content of the first surface is W1, the metal element content of the second surface is W2, and W1 and W2 satisfy the relationship: W1>W2; the metal element includes at least one of Al, Si, Ce, Mg, Zr or Ti.

[0027] According to one embodiment of the present invention, the metal element content of the convex portion is W11, and the metal element content of the concave portion is W21, and the W11 and the W21 satisfy the relationship:

[0028] W11>W21; and / or

[0029] The positive electrode sheet includes a straight portion between two adjacent convex portions; the metal element content of the convex portion is W11, the metal element content of the straight portion is W3, and W11 and W3 satisfy the relationship: W11>W3; and / or

[0030] The positive electrode sheet includes a straight portion between two adjacent convex portions; the metal element content of the straight portion is W3, the metal element content of the concave portion is W21, and W211 and W3 satisfy the relationship:

[0031] W3>W21;

[0032] The metal element includes at least one of Al, Si, Ce, Mg, Zr or Ti.

[0033] According to an embodiment of the present invention, the tensile strength of the positive electrode sheet is ≥100 MPa, and the ratio of the depth (μm) of the recess to the tensile strength (MPa) of the positive electrode sheet is between 0.05 and 0.2.

[0034] According to one embodiment of the present invention, the diaphragm comprises: the ceramic layer is an inorganic ceramic particle coating, a coating of inorganic ceramic particles and PVDF composite, or a coating of inorganic ceramic particles and polymethyl methacrylate and PVDF composite; wherein,

[0035] The inorganic ceramic particles include one or more of α-Al2O3, γ-Al2O3, Al2O3, SiO2, CeO2, MgAl2O4, ZrO, and TiO2;

[0036] The polymethyl methacrylate is in the form of block-shaped or strip-shaped convex structures.

[0037] According to one embodiment of the present invention, the negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer, and the negative electrode active material layer includes a silicon-carbon composite material and / or a silicon-oxygen composite material. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] In order to more clearly illustrate the technical solutions in the embodiments of the present application or the prior art, the drawings required for use in the embodiments or the prior art description are briefly introduced below. Obviously, the drawings described below are some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0039] Figure 1 A schematic diagram of the installation structure of an electrode assembly provided in an embodiment of the present application;

[0040] Figure 2 for Figure 1 Partial cross section of the positive electrode Figure 1 ;

[0041] Figure 3 for Figure 1 Partial cross section of the positive electrode Figure 2 ;

[0042] Figure 4 for Figure 1 Schematic diagram of the projection of the convex and concave parts on the positive electrode sheet;

[0043] Figure 5 for Figure 1 Schematic diagram of the structure per unit area on the positive electrode;

[0044] Figure 6 for Figure 1 Schematic diagram of the distribution structure of the convex area on the positive electrode sheet;

[0045] Figure 7 A schematic diagram of the partial structure of an electrode assembly provided in an embodiment of the present application.

[0046] Reference numerals:

[0047] 100-positive electrode sheet; 110-first surface; 111-convex portion; 120-second surface; 121-concave portion; 130-straight portion; 140-convex portion area; 150-air avoidance area; 151-head air avoidance area; 152-tail air avoidance area; 153-top air avoidance area; 154-bottom air avoidance area; 155-ear air avoidance area; 160-ear; 200-diaphragm; 300-main body area; 400-arc area; 500-negative electrode sheet. DETAILED DESCRIPTION

[0048] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0049] In the related art, a battery includes a cell and an electrolyte that soaks the cell. The cell is composed of a positive electrode sheet, a negative electrode sheet, and a plurality of separators. The separator is bonded to the positive electrode sheet and / or the negative electrode sheet, and the separator separates the positive electrode sheet from the negative electrode sheet.

[0050] However, during the long-term use of the above materials, the electrochemical performance is severely attenuated, the power performance is not satisfactory, and the capacity retention rate is getting worse and worse; on the one hand, the interlayer extrusion of the battery cell is relatively serious, and the electrolyte is difficult to enter, resulting in poor electrolyte infiltration.

[0051] On the other hand, in the environment of high-temperature formation or high-temperature cycle testing, the battery may produce gas (such as hydrogen). If these gases cannot be discharged in time, bubbles will form inside the battery cell. The bubbles will cause pressure increase inside the battery and expansion of the battery cell material, thereby increasing the stress between the interfaces, especially between the electrode and the diaphragm of the battery cell, which is likely to lead to poor interface bonding between the electrode and the diaphragm; especially in the case of high-temperature cycling and high-temperature formation, poor interface bonding will lead to increased local current density between the positive electrode and the diaphragm, thereby aggravating local thermal runaway or structural degradation of the material and forming purple spots, which will seriously affect the appearance of the battery; furthermore, poor interface bonding will also lead to obstructed lithium ion transmission, leading to lithium precipitation, seriously affecting the safety performance of the battery.

[0052] Based on this, an embodiment of the present application provides an electrode assembly and a battery, wherein the electrode assembly includes a positive electrode sheet, a negative electrode sheet and a separator located between the positive electrode sheet and the negative electrode sheet, the positive electrode sheet has a first surface and a second surface opposite to each other in the thickness direction, the first surface has a plurality of protrusions, and the second surface has a plurality of recesses respectively corresponding to the protrusions and recessed toward the protrusions; a separator, the separator includes a first separator and a second separator, the first separator is bonded to the first surface, the second separator is bonded to the second surface, the first separator extends beyond the head end of the positive electrode sheet and the second separator extends beyond the head end of the positive electrode sheet; wherein the bonding force between the first surface and the separator is N1, the bonding force between the second surface and the separator is N2, and N1 and N2 satisfy the relationship: N1>N2.

[0053] During use, the concave portion on the positive electrode sheet increases the storage space for the electrolyte, so as to improve the electrolyte infiltration effect on the entire battery cell after long-term use; and the concave portion can also provide deformation space for the negative electrode, reducing the adverse effects caused by the expansion of the negative electrode material. At the same time, based on the high adhesion between the convex portion and the diaphragm, the gas generated by the electrochemical reaction is preferentially discharged from the weaker adhesion, reducing the possibility of bubbles formed due to gas accumulation inside the battery cell, thereby reducing the possibility of abnormal bonding interface between the first surface and the diaphragm due to gas production, and optimizing battery performance.

[0054] The technical solution of the invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. The following specific embodiments can be combined with each other, and the same or similar concepts or processes may not be repeated in some embodiments.

[0055] like Figure 1 and Figure 2 As shown, an embodiment of the present application provides an electrode assembly, including: a positive electrode sheet 100, a negative electrode sheet 500 and a separator 200, the positive electrode sheet 100 has a first surface 110 and a second surface 120 opposite to each other in the thickness direction, the first surface 110 has a plurality of protrusions 111, and the second surface 120 has a plurality of recesses 121 respectively corresponding to each protrusion 111 and recessed toward the protrusion 111.

[0056] The diaphragm 200 includes a first diaphragm and a second diaphragm. The first diaphragm is bonded to the first surface 110 , and the second diaphragm is bonded to the second surface 120 . The first diaphragm is bonded beyond the head end of the positive electrode sheet 100 .

[0057] The adhesive force between the first surface 110 and the diaphragm 200 is N1, and the adhesive force between the second surface 120 and the diaphragm 200 is N2. N1 and N2 satisfy the relationship: N1>N2.

[0058] It should be noted that each convex portion 111 corresponds to each concave portion 121 one by one.

[0059] During implementation, an embossing roller may be used to extrude the positive electrode sheet 100, so that the positive electrode sheet 100 is deformed and a plurality of protrusions are integrally formed, the outer surface of the protrusion is the protrusion 111, and the inner surface of the protrusion is the concave portion 121. It is understood that the protrusion 111 and the concave portion 121 are integrally formed.

[0060] The adhesive force between the first surface 110 and the diaphragm 200 is N1. The adhesive force between the second surface 120 and the diaphragm 200 is N2, which can be, for example, a comparison of the adhesive force between the convex portion of the first surface and the diaphragm and the adhesive force between the concave portion of the second surface and the diaphragm, or a comparison of the adhesive force between the non-convex portion of the first surface and the diaphragm and the adhesive force between the non-concave portion of the second surface and the diaphragm, or a comparison between the adhesive force between the entire first surface and the diaphragm and the adhesive force between the entire second surface and the diaphragm; N1 and N2 satisfy the relationship: N1>N2. Exemplarily, the relationship between N1 and N2 is preferably N1=(1.01~2)N2, for example, N1=1.005N2, N1=1.01N2, N1=1.5N2, N1=2N2 or other relationships.

[0061] Thus, according to the electrode assembly described in the first aspect of the present application, the convex portion 111 and the concave portion 121 are respectively formed on the two surfaces of the positive electrode sheet 100, so that the surface of the positive electrode sheet 100 is uneven, and the convex portion 111 of the positive electrode sheet 100 has a deformation ability, so that when the battery cell expands, the convex portion 111 can effectively support the diaphragm 200, and prevent the diaphragm 200 or the positive electrode sheet 100 from being deformed by the expansion stress of the negative electrode sheet 500. At the same time, a space for accommodating electrolyte is formed between the convex portion 111 of the positive electrode sheet 100 and the diaphragm 200, thereby increasing the storage space of the electrolyte, improving the infiltration ability of the electrolyte in this area, and avoiding abnormal situations such as insufficient electrolyte and poor infiltration between the positive electrode sheet 100 and the diaphragm 200. Furthermore, the positive electrode sheet 100 forms a concave portion 121, thereby expanding the storage space of the electrolyte, further enhancing the infiltration of the electrolyte, and improving the cycle performance and service life of the electrode assembly.

[0062] In addition, by setting the bonding force between the surface where the convex portion 111 is located (i.e., the first surface 110) and the diaphragm 200 to be greater than the bonding force between the surface where the concave portion 121 is located (i.e., the second surface 120) and the diaphragm 200, a gas discharge path is constructed, so that during the high-temperature formation or high-temperature expansion process, the gas generated by the electrochemical reaction is preferentially discharged from the place where the bonding force is weaker (such as the bonding force between the surface where the concave portion 121 is located and the diaphragm 200, specifically, for example, between each concave portion 121 and the diaphragm 200 or between adjacent concave portions 121 and the diaphragm 200). It can be understood that the diaphragm 200 itself has a certain air permeability, and by forming the convex portion 111 and the concave portion 121 on the positive electrode sheet 100, the distance between the positive electrode sheet 100 and the diaphragm 200 is enlarged. At the same time, the concave portion The smaller the bonding force between the surface where the recess 121 is located and the diaphragm 200, the smaller the bonding area between the surface where the recess 121 is located and the diaphragm 200. The more gaps there are between the surface where the recess 121 is located and the diaphragm 200, the more internal pressure of the battery can be released in time, reducing the possibility of bubbles formed due to gas accumulation inside the battery cell, thereby reducing the possibility of purple spots caused by abnormal bonding interface between the positive electrode sheet 100 and the diaphragm 200 or the diaphragm 200 and the negative electrode sheet 500 in the central area of ​​the electrode assembly due to gas production, thereby maintaining good interface contact between the positive electrode sheet 100 and the diaphragm 200. During the cycle, it is beneficial to more uniform distribution of current density on the positive electrode sheet 100 and the diaphragm 200, avoiding uneven deposition of lithium metal and the resulting formation of lithium dendrites.

[0063] Moreover, by timely discharging the gas through the weaker bonding points, it can also play a heat dissipation role to a certain extent, which is beneficial to maintaining the temperature of the positive electrode sheet 100 during the cycle process, so that the heat inside the battery cell is evenly dispersed, thereby creating a stable reaction environment inside the battery cell and preventing further occurrence of side reactions, thereby improving the cycle performance of the battery and extending the battery life.

[0064] According to one embodiment of the present application, the bonding force between the protrusion 111 and the diaphragm 200 is greater than the bonding force between the straight portion 130 between two adjacent protrusions 111 and the diaphragm 200, so that during high-temperature formation or high-temperature expansion, the gas generated by the electrochemical reaction can also be discharged from the straight portion 130 between adjacent protrusions 111.

[0065] The positive electrode sheet 100 includes a positive electrode current collector and a positive electrode active material layer located on the positive electrode current collector; the negative electrode sheet 500 includes a negative electrode current collector and a negative electrode active material layer located on the negative electrode current collector.

[0066] According to one embodiment of the present application, the negative electrode active material layer includes a silicon-carbon composite material and / or a silicon-oxygen composite material. In one embodiment, the mass proportion of the silicon-carbon composite material and / or the silicon-oxygen composite material in the second active material is less than or equal to 50wt%, for example, 1.5-40wt%.

[0067] The silicon-carbon composite material includes a porous carbon matrix, silicon grains in the pores of the porous carbon matrix, and a carbon layer on the surface of the porous carbon matrix. The present invention can arrange silicon grains in the pores of the porous carbon matrix by deposition, by arranging silicon grains in the pores, and by forming a carbon layer on the surface of the porous carbon matrix, and the carbon layer can be shaped carbon or amorphous carbon. When the silicon grains expand, the interior of the porous carbon matrix can provide sufficient expansion space to prevent the overall structure of the silicon-carbon composite material from deforming, and the carbon layer can constrain the outward expansion force of the porous carbon matrix during the silicon expansion process, ensure the structural strength of the silicon-carbon material, thereby avoiding the problems of cracking, pulverization, and shedding of the negative electrode active layer, and improving the cycle performance and rate performance of the battery.

[0068] In a specific embodiment, the carbon layer includes openings arranged corresponding to the pores of the porous carbon matrix. When the carbon layer is provided with openings, the wettability of the electrolyte to the negative electrode sheet can be improved, and the expansion performance of the silicon-based material can be reduced, thereby reducing the impedance of the battery and improving the cycle performance and rate performance of the battery.

[0069] In a specific embodiment, the specific surface area of ​​the silicon-carbon composite material and / or the silicon-oxygen composite material is 0.5-10 m 2 / g, for example 0.5m 2 / g, 1m 2 / g, 2m 2 / g, 3m 2 / g, 4m 2 / g, 5m 2 / g, 6m 2 / g, 7m 2 / g, 8m 2 / g, 9m 2 / g or 10m 2 When the specific surface area of ​​the silicon-carbon composite material is within the above range, the SEI film formed on the surface of the negative electrode active layer during the charge and discharge process is appropriate, which can reduce the impedance of the battery and improve the cycle performance and rate performance of the battery.

[0070] In a specific embodiment, the particle size Dv50 of the silicon-carbon composite material and / or the silicon-oxygen composite material is 6-15 μm, for example, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm or 15 μm. When the particle size Dv50 of the silicon-carbon composite material and / or the silicon-oxygen composite material is within the above range, the particle size Dv50 of the silicon-carbon composite material is appropriate, which can avoid the situation where the particle size is too small, which easily leads to an increase in the specific surface area of ​​the silicon particles and an increase in side reactions, and can also avoid the situation where the particle size is too large, which easily leads to excessive expansion of the silicon particles, resulting in blocking of the pores of the porous carbon matrix and affecting the infiltration of the electrolyte, thereby improving the cycle performance and rate performance of the battery.

[0071] In a specific embodiment, the powder resistivity of the silicon-carbon composite material and / or the silicon-oxygen composite material is 0.1-1000Ω·cm, for example, 0.1Ω·cm, 0.5Ω·cm, 1Ω·cm, 5Ω·cm, 10Ω·cm, 50Ω·cm, 100Ω·cm, 200Ω·cm, 300Ω·cm, 400Ω·cm, 500Ω·cm, 600Ω·cm, 700Ω·cm, 800Ω·cm, 900Ω·cm or 1000Ω·cm. When the powder resistivity of the silicon-carbon composite material is within the above range, the conductivity of the silicon-carbon composite material is high, which can improve the conductivity of the negative electrode active layer, thereby improving the cycle performance and rate performance of the battery.

[0072] In a specific embodiment, the silicon content in the silicon-carbon composite material and / or the silicon-oxygen composite material is 30-75%, for example, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70% or 75%, etc. When the silicon content in the silicon-carbon composite material and / or the silicon-oxygen composite material is within the above range, it is possible to avoid excessive silicon content in the silicon-carbon composite material and / or the silicon-oxygen composite material, which may lead to excessive expansion of the silicon-carbon composite material and / or the silicon-oxygen composite material, and deformation of the overall structure of the silicon-carbon composite material and / or the silicon-oxygen composite material, thereby avoiding cracking and pulverization of the negative electrode active layer, ensuring the energy of the silicon-carbon composite material and / or the silicon-oxygen composite material, and improving the cycle performance and rate performance of the battery.

[0073] Further, such as Figure 2 As shown, the surface where the protrusion 111 contacts the separator 200 can be set as a curved surface. In this way, in the process of stacking and winding the separator 200 and the positive and negative electrode sheets, the possibility of the protrusion 111 being too sharp and piercing the separator 200 can be avoided, thereby preventing the protrusion of the positive electrode sheet 100 from piercing the separator 200 and contacting the negative electrode sheet 500 and thus short-circuiting.

[0074] Specifically, Figure 2As shown, the convex portion 111 is spherical or quasi-spherical, the radius of the convex portion 111 is R1, and the radius of the concave portion 121 is R2; the positive electrode sheet 100 includes a straight portion 130, and the thickness of the straight portion 130 is H; R1, R2, and H satisfy the relationship: R1>R2; and / or, R1-R2≤H, and / or, R1 / R2=1.01~2.

[0075] It should be noted that the convex portion 111 is equivalent to a spherical shell, R1 is the outer surface radius of the spherical shell, and R2 is the inner surface radius of the spherical shell. The outer surface radius of the spherical shell is greater than the inner surface radius of the spherical shell, R1>R2, and the difference between the outer surface radius of the spherical shell and the inner surface radius of the spherical shell is less than the thickness of the straight portion 130 of the positive electrode sheet 100, that is, R1-R2≤H, that is, the thickness of the convex portion 111 is less than the thickness of the straight portion 130 of the positive electrode sheet 100, thereby improving the deformation capacity of the convex portion 111, so that when the negative electrode sheet 500 expands during the charge and discharge process, the convex portion 111 can effectively relieve the expansion stress of the negative electrode sheet 500 and prevent the negative electrode sheet 500 or the positive electrode sheet 100 from rupturing.

[0076] Further, R1 = 0.5 mm to 8 mm; and / or, R2 = 0.5 mm to 8 mm. Preferably, R1 = 1 mm to 5 mm, R2 = 1 mm to 5 mm.

[0077] Therefore, by limiting the inner and outer surface radii of the protrusion 111 , the projection area of ​​the protrusion 111 in the thickness direction of the positive electrode sheet 100 can be adjusted.

[0078] Exemplarily, R1 can be 0.5mm, 1mm, 3mm, 5mm, 8mm or other values, preferably, R1 = 1mm to 5mm. R2 can be 0.5mm, 1mm, 3mm, 5mm, 8mm or other values, preferably, R2 = 1mm to 5mm. R1 / R2 = 1.01 to 2, R1 / R2 can be 1.01, 1.05, 1.09, 1.1, 2 or other values.

[0079] On the contrary, if R1 or R2 is less than 0.5mm, the projection area of ​​the protrusion 111 is small, which may make the protrusion 111 too sharp and easily pierce the diaphragm 200 and contact the positive electrode sheet 100 on the opposite side, causing a short circuit. In addition, the small projection area of ​​the protrusion 111 may also lead to poor wetting effect on the electrolyte and improvement effect on the expansion of the negative electrode material; if R1 or R2 is greater than 8mm, the projection area of ​​the protrusion 111 is large, which may make the positive electrode sheet 100 easily deformed excessively under the extrusion force of the embossing and the extension force of the electrode sheet itself during the process of forming the protrusion 111, which may easily lead to electrode sheet breakage.

[0080] like Figure 2As shown, in some embodiments, the height from the end point of the convex portion 111 away from the second surface 120 to the surface of the positive electrode sheet 100 is h1; h1 = 3 μm to 40 μm.

[0081] In some embodiments, the distance from the end point of the convex portion 111 away from the flat portion 130 to the surface of the flat portion 130 facing away from the convex portion 111 is less than the radius R1 of the convex portion 111, R3 < R1; in this regard, preferably, R3 < 1 / 5R1.

[0082] Exemplarily, h1 can be 3 μm, 5 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm or other values, preferably, h1 = 5 μm to 30 μm. Thus, by defining the height of the final convex portion 111, a suitable gap can be formed between the positive electrode sheet 100 and the separator 200, so as to reduce the possibility of an increase in the overall thickness while achieving better battery performance.

[0083] As Figure 3 shown, in some embodiments, the curve length of the concave portion 121 in the cross-section passing through the center of the convex portion 111 is C1, and C1 and R2 satisfy the relationship: C1 = πR2.

[0084] It can be understood that since R2 = 0.5 mm to 8 mm, then C1 = 0.5π mm to 8π mm, and preferably, R2 is 1 mm to 5 mm, then C1 is preferably π mm to 5π mm. In this regard, by defining the length of C1, a more appropriate projected area of the convex portion 111 in the thickness direction of the positive electrode sheet 100 can be determined. Additionally, by referring to the values of C1 and R2 simultaneously, the possibility of the convex portion 111 being too large or too small can be reduced, that is, preventing the convex portion 111 from being too large and causing a loss of the volumetric energy density of the battery cell; at the same time, preventing the convex portion 111 from being too small, which may result in a small deformation ability and less deformation space of the convex portion 111 of the positive electrode sheet 100, and a poor improvement effect on the swelling of the negative electrode sheet 500, thus ensuring better use effects.

[0085] In other embodiments, the curve length of the convex portion 111 in the cross-section passing through the center of the convex portion 111 can also be defined.

[0086] As Figure 2 shown, in some embodiments, a plurality of convex portions 111 are spaced apart, and the positive electrode sheet 100 includes a flat portion 130 between two adjacent convex portions 111; the distance between the centers of two adjacent convex portions 111 is L1, and the length of the flat portion 130 between two adjacent convex portions 111 is L2, and L1 and L2 satisfy the relationship: L1 / L2 = 1.05 to 10.

[0087] Exemplarily, L1 / L2 can be 1.05, 1.1, 1.5, 2, 3, 5, 8, 10 or other values, preferably, L1 / L2=1.1-8. By limiting the value of L1 / L2, the density of the protrusions 111 can be ensured, so that the protrusions 111 can provide sufficient support force and deformation space to alleviate the expansion of the negative electrode sheet 500, while ensuring the infiltration effect of the electrolyte. If the ratio is too small, that is, the distance between two adjacent protrusions 111 is too large, it is difficult for the protrusions 111 to alleviate the expansion of the negative electrode sheet 500 and improve the infiltration of the electrolyte; if the ratio is too large, the diameter of the protrusion 111 is too large, resulting in a loss of volume energy density of the battery cell.

[0088] In addition, L1 and L2 can be set to L1 = 2mm ~ 10mm, respectively. Exemplarily, L1 can be 2mm, 3mm, 5mm, 8mm, 10mm or other values. Preferably, L1 = 2mm ~ 8mm; and / or, L2 = 0.5mm ~ 8mm. Exemplarily, L2 can be 0.5mm, 1mm, 3mm, 4mm, 8mm or other values. Preferably, L2 = 1mm ~ 4mm.

[0089] Therefore, by limiting the size of L1 or L2, a suitable spacing can be provided between two adjacent protrusions 111, so as to meet the requirement of adjusting the appropriate volume of the protrusion 111 during the processing.

[0090] On the contrary, if L1<2mm, the convex portions 111 on the positive electrode sheet 100 are densely distributed, that is, the convex points on the roller used for the actual embossing process will also be very dense. In the process of forming the convex portions 111 on the electrode sheet, the extension of the positive electrode sheet 100 is difficult to meet the density of the convex points of the roller, and the stress in the positive electrode sheet 100 is easily concentrated, resulting in local fracture of the positive electrode sheet 100; and the height of the convex portion 111 is also difficult to meet, so that the deformation space of the convex portion 111 is small. If L1>8mm, that is, the convex points of the roller for embossing are too sparse, the convex portions 111 on the positive electrode sheet 100 are too dispersed and the supporting surface is insufficient, and it is difficult to achieve a better bonding effect between the first surface 110 and the separator 200.

[0091] In some embodiments, the area of ​​the convex portion 111 is Q1, the area of ​​the concave portion 121 is Q2, and Q1 and Q2 satisfy the relationship: Q1 / Q2=1.02-1.21;

[0092] and / or, if Figure 4 As shown, the projection area of ​​the convex portion 111 in the thickness direction of the positive electrode sheet 100 is S1, and the projection area of ​​the concave portion 121 in the thickness direction of the positive electrode sheet 100 is S2. S1 and S2 satisfy the relationship: S1 / S2=1.02~1.21.

[0093] It should be noted that Q1=2πR12 , Q2=2πR2 2 ; then Q1 / Q2=R1 2 / R2 2 . S1=πR1 2 , S2=πR2 2 ; then S1 / S2=R1 2 / R2 2 Here, Q1 / Q2 and S1 / S2 are both set to 1.02 to 1.21.

[0094] Exemplarily, Q1 / Q2 or S1 / S2 may be 1.02, 1.1, 1.5, 1.21 or other values.

[0095] Therefore, by controlling the ratio between Q1 and Q2, or the ratio between S1 and S2, it can ensure that the protrusion 111 of the positive electrode sheet 100 has sufficient deformation space to alleviate the expansion of the negative electrode sheet 500, and it can also ensure that the protrusion 111 of the positive electrode sheet 100 and the diaphragm 200 have a larger bonding area, and the bonding force between the protrusion 111 and the diaphragm 200 is better.

[0096] like Figure 5 As shown, in some embodiments, the number of protrusions 111 per unit area of ​​the positive electrode sheet 100 is N, and N satisfies the relationship: 2≤N≤25.

[0097] Exemplarily, N may be 2, 4, 6, 8, 9, 15, 25 or other values, preferably, 4≤N≤15.

[0098] Among them, the unit area is 1, 2, 3, 4, 5 cm 2 . Thus, by controlling the number of protrusions 111 per unit area, the density of the protrusions 111 can be reasonably set. This can reduce the poor improvement effect on the electrolyte infiltration or the alleviation of the expansion of the negative electrode sheet 500 due to too few protrusions 111; or due to too many protrusions 111, in the process of embossing the protrusions, the pressure of the roller is likely to exceed the tensile strength of the positive electrode sheet 100, resulting in the height of the protrusions 111 failing to reach the preferred value, and even causing the positive electrode sheet 100 to break.

[0099] In some embodiments, the total projection area of ​​each protrusion 111 in the thickness direction of the positive electrode sheet 100 per unit area is S3, and the proportion of S3 per unit area satisfies the relationship: 0.2≤S3≤0.8.

[0100] Exemplarily, S3 may be 0.2, 0.4, 0.5, 0.6, 0.7, 0.8 or other values, preferably, 0.4≤S3≤0.6.

[0101] Among them, the unit area is 1, 2, 3, 4, 5 cm2 Thus, by controlling the area of ​​the convex portion 111 per unit area and then reasonably setting the density of the convex portion 111, the improvement effect on the electrolyte infiltration or the alleviation of the expansion of the negative electrode sheet 500 due to the small area of ​​the convex portion 111 is reduced; or due to the large area of ​​the convex portion 111, in the process of embossing the convex portion 111, the pressure of the roller is likely to exceed the tensile strength of the positive electrode sheet 100, resulting in the height of the convex portion 111 failing to reach the preferred value, and even causing the positive electrode sheet 100 to break.

[0102] like Figure 6 As shown, in some embodiments, the area on the positive electrode sheet 100 where the protrusions 111 are concentrated is the protrusion area 140, the total area of ​​the protrusion area 140 is S11, the total area of ​​the positive electrode sheet 100 is S, and S11 and S satisfy the relationship: 0.02≤S11 / S≤0.85.

[0103] Illustratively, S11 / S may be 0.02, 0.1, 0.3, 0.6, 0.85 or other values.

[0104] It should be noted that the area on the positive electrode sheet 100 where the protrusions 111 are concentrated is the protrusion area 140, and the length of the protrusion area 140 refers to the distance between the first protrusion 111 and the last protrusion 111 in the protrusion area 140 along the length direction; the width of the protrusion area 140 refers to the distance between the first protrusion 111 and the last protrusion 111 in the protrusion area 140 along the width direction.

[0105] Therefore, the proportion of the total area of ​​the convex region 140 to the total area of ​​the positive electrode sheet 100 is set so as to reasonably control the size of the distribution area of ​​the convex portion 111 on the positive electrode sheet 100, thereby ensuring that the positive electrode sheet 100 has a better use effect.

[0106] On the contrary, if S11 / S is too large (i.e. greater than 0.85), the area of ​​the convex region 140 is too large, and in the process of embossing to form the convex portion 111, the pressure of the roller is likely to exceed the tensile strength of the positive electrode sheet 100, thereby causing the height of the convex portion 111 to fail to reach the preferred value, and even causing the positive electrode sheet 100 to break; if S11 / S is too small (i.e. less than 0.02), the convex portion 111 has poor improvement effect on the wetting effect of the electrolyte or on alleviating the expansion of the negative electrode sheet 500.

[0107] Furthermore, the distance between the protrusion area 140 and the two end edges of the positive electrode sheet 100 in the length direction is K, K=10mm~100mm; and / or, the distance between the protrusion area 140 and any end edge of the positive electrode sheet 100 in the width direction is M, M=5mm~30mm.

[0108] In the embodiment of the present application, the area on the positive electrode sheet 100 where the protrusion 111 is not provided is the air avoidance area 150. The positive electrode sheet 100 extends horizontally, and the air avoidance area 150 may include a head air avoidance area 151, a tail air avoidance area 152, a top air avoidance area 153 and / or a bottom air avoidance area 154.

[0109] The head avoidance area 151 is an area between the convex area 140 and the head of the positive electrode sheet 100 , and the distance between the convex area 140 and the head of the positive electrode sheet 100 is K1 , where K1 = K = 10 mm to 100 mm.

[0110] The tail avoidance area 152 is the area between the convex area 140 and the tail of the positive electrode sheet 100. The distance between the convex area 140 and the tail of the positive electrode sheet 100 is K2, K2=K=10mm-100mm. In implementation, the tail avoidance area 152 can also be the area between the convex area 140 and the intersection of the single-sided area and the double-sided area of ​​the tail of the positive electrode sheet 100.

[0111] Exemplarily, K1 or K2 may be 10 mm, 30 mm, 60 mm, 80 mm, 100 mm or other values.

[0112] The bottom clearance area 154 is an area between the convex area 140 and the bottom edge of the positive electrode sheet 100. The distance between the convex area 140 and the bottom edge of the positive electrode sheet 100 is M1, where M1=M=5 mm to 30 mm.

[0113] The top avoidance area 153 is an area between the convex area 140 and the top edge of the positive electrode sheet 100 . The distance between the convex area 140 and the top edge of the positive electrode sheet 100 is M2 , where M2=M=5 mm to 30 mm.

[0114] Exemplarily, M1 or M2 may be 5 mm, 10 mm, 15 mm, 20 mm, 30 mm or other values. Preferably, M1 or M2 = 5 mm to 20 mm.

[0115] Therefore, setting a suitable air-avoiding area 150 at the edge of the positive electrode sheet 100 can ensure the better performance of the positive electrode sheet 100 itself. The top air-avoiding area 153 and the bottom air-avoiding area 154 can reduce the possibility of edge curling and poor interface uniformity caused by rolling stress at the edge of the positive electrode sheet 100, and can also prevent the edge of the positive electrode sheet 100 from losing powder during the embossing process; the head air-avoiding area 151 can improve the stability of the head of the positive electrode sheet 100, and can prevent the head from being folded when entering the sheet, and the problem of unstable structure caused by unstable sheet entry during winding; in implementation, foil is usually set at the tail of the positive electrode sheet 100, and the tail air-avoiding area 152 can reduce the possibility of foil damage.

[0116] On the contrary, if K1 or K2 is less than 10 mm, and M1 or M2 is less than 5 mm, the convex region 140 covers too wide, so that the positive electrode sheet 100 is prone to cracking or deformation or wrinkling at the head and tail during subsequent processing, making it difficult to roll. If K1 or K2 is greater than 100 mm, and M1 or M2 is greater than 30 mm, the convex region 140 covers a narrower area, and the number of convex portions 111 is small, resulting in poor improvement of the convex portions 111 in terms of the electrolyte infiltration effect or the effect of alleviating the expansion of the negative electrode sheet 500.

[0117] like Figure 6 As shown, in some embodiments, a tab 160 is disposed on the positive electrode sheet 100 , and a distance between the protrusion region 140 and the tab 160 is J, where J=5 mm to 30 mm.

[0118] Exemplarily, J may be 5 mm, 10 mm, 25 mm, 30 mm or other values.

[0119] In practice, in order to facilitate the connection of the positive electrode sheet 100 with other components, a tab 160 is often provided on the positive electrode sheet 100 to provide a connection point. In this embodiment, the tab 160 is provided on the top edge of the positive electrode sheet 100 by welding, bonding or other methods, and the clearance area 150 also includes a tab clearance area 155.

[0120] The convex region 140 includes at least two spaced-apart unit regions, and the tab 160 is located between two adjacent unit regions. On this basis, the tab avoidance region 155 is the region between the tab 160 and the adjacent unit region, and the spacing between the tab 160 and the adjacent unit regions on both sides is J1 and J2, J1=J=5mm-30mm, J2=J=5mm-30mm.

[0121] Therefore, the tab avoidance area 155 can ensure the stability of the tab 160 , and avoid the tab 160 from crushing the underlying current collector during embossing and rolling on the tab 160 , thereby affecting the welding effect of the tab 160 .

[0122] like Figure 1 As shown, in some embodiments, the positive electrode sheet 100, the separator 200 and the negative electrode sheet 500 are stacked and wound to form a core structure, and the electrode assembly includes a main body area 300 and an arc area 400; the height of the protrusion 111 located in the arc area 400 is less than the height of the protrusion 111 located in the main body area 300.

[0123] During implementation, the battery is configured as a winding core structure, so the positive electrode sheet 100 needs to be wound. At this time, the height of the convex portion 111 in the arc region 400 is set to be smaller than the height of the convex portion 111 in the main region 300, which can ensure that the arc region 400 of the positive electrode sheet 100 is not prone to breakage during the winding process, and can also prevent the convex portion 111 in the arc region 400 from being too large to affect the overall width of the battery cell, thereby affecting the energy density of the battery cell.

[0124] Exemplarily, the ratio of the height of the protrusion 111 in the main body area 300 to the height of the protrusion 111 in the arc area 400 can be 1.05, 1.1, 1.5, 1.8, 2, or 3. Preferably, the ratio of the height of the protrusion 111 in the main body area 300 to the height of the protrusion 111 in the arc area 400 can be set to 1.1 to 2.

[0125] In some embodiments, the diaphragm 200 includes: a base film, the base film includes a multi-layer microporous film, wherein the base film includes several layers of PE (polyethylene) microporous film, PP (polypropylene) microporous film and PP and PE composite microporous film. A ceramic layer, the ceramic layer is coated on the base film, and the ceramic layer and the positive electrode sheet 100 are arranged relative to each other, that is, the ceramic layer and the protrusion 111 of the positive electrode sheet 100 are arranged relative to each other. Considering that the top of the protrusion 111 is too sharp and punctures the diaphragm 200, the ceramic layer in the diaphragm 200 will cover the top of the protrusion 111, so that even if the protrusion 111 of the positive electrode sheet 100 contacts the negative electrode sheet 500, the ceramic layer can isolate the positive electrode sheet 100 and the negative electrode sheet 500, thereby improving the safety performance of the battery cell.

[0126] In some examples, the diaphragm 200 includes: the ceramic layer is an inorganic ceramic particle coating, a coating of inorganic ceramic particles and PVDF composite, or a coating of inorganic ceramic particles and polymethyl methacrylate, PVDF composite; wherein the inorganic ceramic particles include one or more of α-Al2O3, γ-Al2O3, Al2O3, SiO2, CeO2, MgAl2O4, ZrO, TiO2; and the polymethyl methacrylate is a raised structure distributed in blocks or strips.

[0127] During implementation, the inorganic ceramic particles in the separator 200 can improve the hidden dangers caused by the die-cutting burrs of the positive electrode sheet 100. In addition, the inorganic ceramic particles can also neutralize the HF decomposed in the electrolyte, improve the liquid retention capacity of the positive electrode sheet 100, and thus improve the battery cycle performance. In addition, it can also reduce the possibility of the convex portion 111 piercing the separator 200 to cause a short circuit, thereby improving the battery safety performance.

[0128] In some embodiments, the metal element content of the first surface 110 is W1, and the metal element content of the second surface 120 is W2, W1 and W2 satisfy the relationship: W1>W2; the metal element includes at least one of Al, Si, Ce, Mg, Zr or Ti.

[0129] At this time, the metal content of the first surface 110 is greater than the metal content of the second surface 120, and the metal element includes at least one of Al, Si, Ce, Mg, Zr or Ti. It is understandable that the ceramic layer and the positive electrode sheet 100 are arranged relative to each other, that is, the ceramic layer and the protrusion 111 of the positive electrode sheet 100 are arranged relative to each other, and the inorganic ceramic content can be mainly characterized by the content of Al, Si, Ce, Mg, Zr, and Ti. It is understandable that by limiting these elements, the content of inorganic ceramics on the first surface 110 and the content of inorganic ceramics on the second surface 120 are characterized, that is, the content of inorganic ceramics on the first surface 110 is greater than the content of inorganic ceramics on the second surface 120. Since the force applied to the protrusion 111 of the positive electrode sheet 100 is greater, the inorganic ceramic material usually increases the mechanical strength of the surface where the protrusion 111 of the positive electrode sheet 100 is located, improves the structural stability of the surface, and prevents the protrusion 111 of the positive electrode sheet 100 from being easily deformed by the expanded negative electrode sheet 500 when the negative electrode sheet 500 expands. Moreover, the content of the inorganic ceramic on the first surface 110 is greater than that on the second surface 120, and the bonding force between the first surface 110 and the diaphragm 200 can be improved, so that the stability of the first surface 110 and the diaphragm 200 when bonded is relatively high. Exemplarily, W1 can be set to 1.02W2, 1.05W2, 1.2W2, 1.4W2, 1.5W2, 2W2 or other values, preferably, W1=(1.05-1.5)W2.

[0130] Further, the metal element content of the convex portion 111 is W11, the metal element content of the concave portion 121 is W21, W11 and W21 satisfy the relationship: W11>W21; and / or, the positive electrode sheet 100 includes a straight portion 130 between two adjacent convex portions 111; the metal element content of the convex portion 111 is W11, the metal element content of the straight portion 130 is W3, W11 and W3 satisfy the relationship: W11>W3; and / or, the positive electrode sheet 100 includes a straight portion 130 between two adjacent convex portions 111; the metal element content of the straight portion 130 is W3, the metal element content of the concave portion is W21, W211 and W3 satisfy the relationship: W3>W21; the metal element includes at least one of Al, Si, Ce, Mg, Zr or Ti.

[0131] It is understandable that the ceramic layer and the positive electrode sheet 100 are arranged relative to each other, that is, the ceramic layer and the protrusions of the positive electrode sheet 100 are arranged relative to each other, and the inorganic ceramic content can be mainly characterized by the content of Al, Si, Ce, Mg, Zr, and Ti. It is understandable that by limiting these elements, the inorganic ceramic content of the protrusions 111, the recesses 121, and the straight portions 130 is characterized, that is, the inorganic ceramic content of the protrusions 111 is greater than that of the straight portions 130, which is greater than that of the recesses 121, thereby ensuring the bonding force between the recesses 121, the straight portions 130, and the recesses 121 and the diaphragm 200; in addition, since the force exerted on the protrusion area 140 of the positive electrode sheet 100 is greater, the inorganic ceramic material usually increases the mechanical strength of the surface where the protrusions 111 of the positive electrode sheet 100 are located, improves the structural stability of the surface, and prevents the protrusions 111 of the positive electrode sheet 100 from being easily deformed by the expanded negative electrode sheet 500 when the negative electrode sheet 500 expands. Finally, it is also possible to ensure that a gas discharge path is constructed so that during high-temperature formation or high-temperature expansion, the gas generated by the electrochemical reaction is preferentially discharged from a place where the bonding force is weaker (such as the bonding force between the surface where the recess 121 is located and the diaphragm 200, specifically, for example, between each recess 121 and the diaphragm 200 or between the straight portion 130 and the diaphragm 200). It is understandable that the diaphragm 200 itself has a certain air permeability, and by forming the convex portion 111 and the concave portion 121 on the positive electrode sheet 100, the air permeability between the positive electrode sheet 100 and the diaphragm 200 is enlarged. At the same time, the bonding force between the surface where the recess 121 is located and the diaphragm 200 is smaller, which means that the bonding area between the surface where the recess 121 is located and the diaphragm 200 is relatively small, and there are more gaps between the surface where the recess 121 is located and the diaphragm 200, so that the internal pressure of the battery can be released in time, reducing the possibility of bubbles formed due to gas accumulation inside the battery cell, and further reducing the possibility of purple spots caused by abnormal bonding interface between the positive electrode sheet 100 and the diaphragm 200 or the diaphragm 200 and the negative electrode sheet 500 due to gas production in the central area of ​​the electrode assembly.

[0132] Exemplarily, W11 can be set to 1.02W21, 1.05W21, 1.2W21, 1.4W21, 1.5W21, 2W21 or other values; W11 can be set to 1.03W3, 1.05W3, 1.3W3, 1.4W3, 2W3 or other values. Preferably, W11=(1.05~1.4)W3=(1.05~1.5)W21.

[0133] In some embodiments, the tensile strength of the positive electrode sheet 100 is ≥100 MPa, and the ratio of the depth (μm) of the recess 121 to the tensile strength (MPa) of the positive electrode sheet 100 is between 0.05 and 0.2.

[0134] Specifically, the tensile strength of the positive electrode sheet 100 in the transverse direction (TD) and the tensile strength in the longitudinal direction (MD) are set to 100 MPa or above. For example, the tensile strength of the positive electrode sheet 100 can be 100 MPa, 110 MPa, 1500 MPa or other values. This can ensure the strength of the positive electrode sheet 100 itself, so as to reduce the possibility of cracking of the positive electrode sheet 100 during subsequent rolling of the convex portion 111 or winding. In addition, the ratio of the depth (μm) of the concave portion 121 to the tensile strength (MPa) of the positive electrode sheet 100 is set in a preferred range, which can be between 0.05 and 0.2, wherein it can be 0.05, 0.1, 0.15, 0.2 or other values. Of course, the ratio of the depth (μm) of the concave portion 121 to the tensile strength (MPa) of the current collector can also be set between 0.05 and 0.2.

[0135] It is understandable that, if the depth of the recess 121 is greater, the compressive stress applied to the positive electrode sheet 100 is greater, and thus the tensile strength of the positive electrode sheet 100 should be greater to reduce the possibility of cracking of the positive electrode sheet 100 .

[0136] On the contrary, if the ratio of the depth (μm) of the concave portion 121 to the tensile strength (MPa) of the positive electrode sheet 100 is less than 0.05, the tensile strength of the positive electrode sheet 100 is set relatively high, which is prone to material waste and high cost. If the ratio of the depth (μm) of the concave portion 121 to the tensile strength (MPa) of the positive electrode sheet 100 is greater than 0.2, during the rolling process of the convex portion 111, the positive electrode sheet 100 is difficult to meet the required tensile strength, which is prone to cracking of the positive electrode sheet 100.

[0137] In summary, an electrode assembly provided by an embodiment of the present application increases the storage space for the electrolyte through the recess 121 on the positive electrode sheet 100 during use, so as to improve the infiltration effect of the electrolyte on the entire battery cell after long-term use; and the recess 121 can also provide deformation space for the negative electrode sheet 500, reducing the adverse effects caused by the expansion of the negative electrode material. At the same time, on the basis of the high adhesion between the convex portion 111 and the diaphragm 200, the gas generated by the electrochemical reaction is preferentially discharged from the weaker adhesion (such as the adhesion between the surface where the recess 121 is located and the diaphragm 200, specifically, for example, between each recess 121 and the diaphragm 200 or between the straight portion 130 and the diaphragm 200), reducing the possibility of bubbles formed due to gas accumulation inside the battery cell, thereby reducing the possibility of abnormal bonding interface between the first surface 110 and the diaphragm 200 due to gas production, and optimizing battery performance.

[0138] like Figure 7 As shown, an embodiment of the present application further provides a battery, comprising the electrode assembly in any one of the above embodiments, wherein the separator 200 in the electrode assembly is clamped between the negative electrode sheet 500 and the positive electrode sheet 100 .

[0139] It should be noted that the battery also includes a shell and an electrolyte, and the electrode assembly and the electrolyte are both arranged in the shell, which are not shown in the drawings.

[0140] The electrode assembly is in a winding structure, and the negative electrode sheet 500 and the positive electrode sheet 100 are respectively bonded to both sides of the separator 200, so that the separator 200 separates the negative electrode sheet 500 from the positive electrode sheet 100. The specific structure of the positive electrode sheet 100 has been described in detail in the above embodiment and will not be repeated here.

[0141] In actual use, the concave portion 121 on the positive electrode sheet 100 increases the storage space for the electrolyte; and the concave portion 121 can also provide deformation space for the negative electrode sheet 500. At the same time, the gas generated by the electrochemical reaction is preferentially discharged from the gaps between the convex portions 111, reducing the possibility of bubbles formed due to gas accumulation inside the battery cell, thereby reducing the possibility of abnormal bonding interface between the first surface 110 and the separator 200 due to gas generation, thereby optimizing battery performance.

[0142] During implementation, the positive electrode sheet 100, the negative electrode sheet 500 and the battery having the convex portion 111 structure are respectively manufactured according to the following methods:

[0143] Preparation method of positive electrode sheet 100:

[0144] For example, lithium cobalt oxide, a conductive agent (a mixture of conductive carbon black and carbon nanotubes), and PVDF (polyvinylidene fluoride) are placed in NMP (methyl pyrrolidone) at a mass ratio of 97.60:1.35:1.05, and stirred evenly to prepare a positive electrode slurry. The positive electrode slurry is evenly coated on both sides of an aluminum foil, with a coating surface density of 0.01704 g / cm2; after drying and rolling treatment in sequence, a positive electrode sheet 100 with a double-sided thickness of 90 μm is prepared; the cut positive electrode sheet 100 is embossed with an embossing roller having a convex portion 111.

[0145] Preparation method of negative electrode sheet 500:

[0146] Exemplarily, silicon-containing artificial graphite, conductive carbon black, styrene-butadiene rubber, and sodium carboxymethyl cellulose are placed in deionized water at a mass ratio of 97.2:0.5:1.3:1, wherein the silicon content in the silicon-containing artificial graphite is 5%; the above slurry is stirred evenly to obtain a negative electrode slurry; the negative electrode slurry is evenly coated on the negative electrode collector, and the negative electrode sheet 500 is obtained after drying, rolling, slitting, washing, and sheeting.

[0147] Battery preparation method:

[0148] In the embodiment of the present application, the separator 200 is 9 μm thick. The electrolyte includes lithium salt LiPF6 and a solvent, and the solvent includes ethylene carbonate (EC), diethyl carbonate (DEC) and ethyl methyl carbonate (EMC), wherein the molar ratio of the three is DEC:EC:EMC=1:1:1. The above-cut positive electrode sheet 100, separator 200, and negative electrode sheet 500 are stacked in sequence and wound into a wound structure battery cell, and the battery cell is packaged, injected, formed, and sealed to obtain a battery.

[0149] Battery performance test method:

[0150] Liquid retention test: Each battery is filled with a certain amount of liquid, for example, the liquid filling amount n1 of each battery is 8.5g±0.1g. After filling, it is aged, and after aging, it is formed - sorted and sealed twice. The second sealing is to extract excess electrolyte, and the remaining electrolyte volume is the liquid retention volume n2; then n2 = (weight after second sealing m2-weight before filling m1).

[0151] Appearance test of the positive electrode sheet 100 after the protrusion 111 is processed: the positive electrode sheet after the protrusion 111 is processed is observed using a 3D microscope to observe whether there is any damage and the size of the damaged area.

[0152] Test of the adhesion between the positive electrode sheet 100 and the diaphragm 200: According to the experimental method, the positive electrode sheet 100, the negative electrode sheet 500 and the diaphragm 200 are assembled together through a winding process to form a battery cell, and the assembled battery cell is subjected to hot pressing treatment. The hot pressing temperature is 70°C, the hot pressing pressure is 1.5Mpa, and the hot pressing time is 15S; take the bare battery cell after hot pressing, and cut the diaphragm 200 and the positive electrode sheet 100 into a matrix size of 5 cm in width and 5 cm in length along the MD (longitudinal) direction of the diaphragm 200 using a cutter, and use a tensile tester to test the peeling force between the diaphragm 200 coating relative to the first surface 110 and the second surface 120.

[0153] Test of the content of inorganic ceramic particles on the positive electrode 100: The inorganic ceramic content can be mainly characterized by the content of Al, Si, Ce, Mg, Zr or Ti, and can be tested with reference to the EDS in the existing SEM (i.e., energy dispersive X-ray spectroscopy (EDS) in a scanning electron microscope (SEM)).

[0154] Cycle retention rate and expansion change rate test: The battery was tested for electric cycle in a blue electric test cabinet. The test conditions were 25℃±2℃, 3.2C charge to 4.37V, 2.8C charge to 4.37V, 2C charge to 4.53V, 1.5C charge to 4.58V, cut off at 0.05C; 0.7C discharge to 3V; the specific charging system was: stand at 25℃±2℃ for 5 minutes, 0.2C discharge to the lower limit voltage; stand for 5 minutes, 0.7C charge to the upper limit voltage, cut off at 0.025C, stand for 5 minutes, 0.2C discharge to the lower limit voltage. For the initial capacity test, stand for 5 minutes, 3.2C charge to 4.37V, 2.8C charge to 4.37V, 2C charge to 4.53V, 1.5C charge to 4.58V, cut off at 0.05C, measure and record the data under full charge state, voltage, thickness. Stand for 5min at 25℃±2℃, discharge 3V at 0.7C, stand for 5min, charge 4.37V at 3.2C, charge 4.37V at 2.8C, charge 4.53V at 2C, charge 4.58V at 1.5C, cut off at 0.05C, stand for 5min, discharge 3V at 0.7C, stand for 5min, 8~9 1200 times, repeat 3~4 steps for capacity test at 25℃ every 100 times, first 200T: measure the voltage and thickness of the fully charged cell every 50T, after 200T: measure the voltage and thickness of the fully charged cell every 100T, and then test the cycle retention rate and expansion change rate of the battery at 200T and 400T. The expansion change rate of the battery = (the full-charge thickness of the battery after N cycles - the thickness of the battery sample) / the thickness of the battery sample * 100%), the thickness of the battery sample is the initial thickness of the battery before the cycle starts.

[0155] Among them, the cycle retention rate refers to the ratio of the remaining capacity of the battery to the initial capacity after a certain number of charge and discharge cycles, usually expressed as a percentage; the expansion change rate refers to the thickness change caused by the battery during the charge and discharge process, usually expressed as a percentage.

[0156] The present invention is described in detail through examples, and the present invention includes but is not limited to the following examples. The following examples and comparative examples are all based on the thickness of the positive electrode sheet 100 being 90 μm, the thickness of the separator 200 being 9 μm, and the silicon content of the negative electrode sheet 500 being 20%. At the same time, according to the radius R1 of the convex portion 111 = 0.5 mm to 8 mm, the radius R2 of the concave portion 121 = 0.5 mm to 8 mm, the height h1 of the convex portion 111 = 3 μm to 40 μm, and the proportion of the total area of ​​the convex region 140 to the total area of ​​the positive electrode sheet 100 S11 / S = 0.02 to 0.85. Compare the effects of different convex portion 111 sizes (such as R1, R2, h1) and the proportion S11 / S of the total area of ​​the convex region 140 to the total area of ​​the positive electrode sheet 100 on battery performance.

[0157] Embodiment 1:

[0158] In this embodiment, the radius R2 of the recess 121 is 0.5 mm, R1 / R2 is 1.01-1.1, where R1 / R2 is 1.05, the radius R1 of the protrusion 111 is 0.52 mm, the height h1 of the protrusion 111 is 20 μm, and the total area of ​​the protrusion region 140 accounts for S11 / S=0.7 of the total area of ​​the positive electrode sheet 100.

[0159] Embodiment 2:

[0160] In this embodiment, R2=1 mm, R1=1.05 mm, and other conditions remain unchanged from those in Embodiment 1.

[0161] Embodiment 3:

[0162] In this embodiment, R2=3 mm, R1=3.15 mm, and other conditions remain unchanged from those in Embodiment 1.

[0163] Embodiment 4:

[0164] In this embodiment, R2=4 mm, R1=4.2 mm, and other conditions remain unchanged from those in Embodiment 1.

[0165] Embodiment 5:

[0166] In this embodiment, R2=7 mm, R1=7.35 mm, and other conditions remain unchanged from those in Embodiment 1.

[0167] Comparative Example 1:

[0168] In this embodiment, R2=0.2 mm, R1=0.21 mm, h1=1 μm, S11 / S=1.01, and other conditions remain unchanged from those in Embodiment 1.

[0169] Comparative Example 2:

[0170] In this embodiment, R2=0.2 mm, R1=0.21 mm, h1=50 μm, S11 / S=0.9, and other conditions remain unchanged from those in Embodiment 1.

[0171] Comparative Example 3:

[0172] In this embodiment, R2=9 mm, R1=9.45 mm, h1=1 μm, S11 / S=0.01, and other conditions remain unchanged from those in Embodiment 1.

[0173] Comparative Example 4:

[0174] In this embodiment, R2=9 mm, R1=9.45 mm, h1=50 μm, S11 / S=0.9, and other conditions remain unchanged from those in Embodiment 1.

[0175] Comparative Example 5:

[0176] In this embodiment, R2=0 mm, R1=0 mm, h1=0 μm, S11 / S=0, and other conditions remain unchanged from those in Embodiment 1.

[0177] Comparative Example 6:

[0178] In this embodiment, the silicon content in the negative electrode sheet 500 is set to 70%, and other conditions remain unchanged from those in Embodiment 5.

[0179] The positive electrode sheet 100, the separator 200, the negative electrode sheet 500 and the electrolyte provided in the above embodiments and comparative examples are combined to form a battery as a whole, and then the battery's liquid retention, cycle retention rate and expansion change rate are tested using the above test method. The results are shown in Table 1.

[0180] Table 1

[0181]

[0182] As can be seen from Table 1, compared with a battery made of a positive electrode sheet 100 without a protrusion 111, a battery made of a positive electrode sheet 100 with a protrusion 111 has an increased electrolyte storage space and a relatively increased liquid retention amount, so as to improve the electrolyte infiltration effect on the entire battery cell after long-term use. At the same time, when the size of the protrusion 111 is different, the battery has different liquid retention amounts, different cycle retention rates, and different expansion change rates. Compared with Comparative Example 5, when R1 or R2 is less than 0.5 mm, h1 is less than 3 μm, and S11 / S is less than 0.02, the change in liquid retention amount is not obvious, the change in cycle retention rate is not obvious, and the expansion change rate does not change significantly, and the improvement effect on the battery is not good. When R1 or R2 is greater than 8mm, h1 is greater than 40μm, and S11 / S is greater than 0.85, the liquid retention amount increases, the cycle retention rate increases, and the expansion change rate decreases, but it is easy to cause the battery thickness to increase; when R1 or R2 is greater than 8mm and h1 is less than 3μm, the thickness of the convex portion 111 is difficult to meet the requirements and collapse is likely to occur. When R1 = 0.5mm ~ 8mm, R2 = 0.5mm ~ 8mm, h1 = 3μm ~ 40μm, S11 / S = 0.02 ~ 0.85, the liquid retention amount increases, the cycle retention rate increases, and the expansion change rate decreases, which significantly improves the battery performance. At this time, the convex portion 111 itself has a better thickness, which can reduce the possibility of collapse of the convex portion 111.

[0183] In addition, the test results in each embodiment show that the battery expansion rate is relatively low, which reflects that the positive electrode sheet 100 with the protrusion 111 provides a certain space for the expansion of the negative electrode sheet 500. At the same time, by comparing the parameters in Example 5 and Comparative Example 6, it can be seen that when the silicon content is large, the influence on the battery expansion change rate is greater.

[0184] Therefore, the recess 121 on the positive electrode sheet 100 increases the storage space for the electrolyte, so as to improve the infiltration effect of the electrolyte on the entire battery cell after long-term use; and the recess 121 can also provide deformation space for the negative electrode sheet 500, reduce the adverse effects caused by the expansion of the negative electrode sheet 500 material, and optimize the battery performance.

[0185] In the description of the present application, it should be understood that the terms "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside" and the like indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present application and simplifying the description, and do not indicate or imply that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on the present application.

[0186] In the description of the present application, it should be understood that the terms "including" and "having" and any variations thereof used in the embodiments of the present application are intended to cover non-exclusive inclusions. For example, a process, method, system, product or apparatus comprising a series of steps or units is not necessarily limited to those steps or units clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or apparatuses.

[0187] Unless otherwise expressly specified and limited, the terms "installed", "connected", "connected", "fixed", etc. should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or integrated; it can be directly connected or indirectly connected through an intermediate medium, and it can make the internal connection of two elements or the interaction relationship between two elements. For ordinary technicians in this field, the specific meanings of the above terms in this application can be understood according to the specific circumstances. In addition, the terms "first", "second", etc. are used for descriptive purposes only and cannot be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features.

[0188] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.

Claims

1. An electrode assembly, characterized in that: include: A positive electrode sheet (100), a negative electrode sheet (500), and a separator (200) located between the positive electrode sheet (100) and the negative electrode sheet (500); The positive electrode sheet (100) has a first surface (110) and a second surface (120) which are opposite to each other in the thickness direction, the first surface (110) has a plurality of convex portions (111), and the second surface (120) has a plurality of concave portions (121) which respectively correspond to the convex portions (111) and are concave toward the convex portions (111); The diaphragm (200) comprises a first diaphragm and a second diaphragm; the first diaphragm is bonded to the first surface (110), and the second diaphragm is bonded to the second surface (120); the first end of the first diaphragm extending beyond the positive electrode sheet (100) and the second end of the second diaphragm extending beyond the positive electrode sheet (100) are bonded; The adhesive force between the first surface (110) and the diaphragm (200) is N1, and the adhesive force between the second surface (120) and the diaphragm (200) is N2, and N1 and N2 satisfy the relationship: N1>N2.

2. The electrode assembly according to claim 1, characterized in that: The N1=(1.01~2)N2.

3. The electrode assembly according to claim 1, characterized in that: The surface of the convex portion (111) in contact with the diaphragm (200) is a curved surface.

4. The electrode assembly according to claim 1, characterized in that: The convex portion (111) is spherical or quasi-spherical, the radius of the convex portion (111) is R1, and the radius of the concave portion (121) is R2; The R1 and R2 satisfy the relationship: R1 / R2=1.01~2.

5. The electrode assembly according to claim 4, characterized in that: R1 = 0.5 mm to 8 mm; And / or, R2=0.5 mm to 8 mm; and / or, the height from the end point of the protrusion (111) away from the second surface (120) to the surface of the positive electrode sheet (100) is h1; h1=3 μm to 40 μm.

6. The electrode assembly according to claim 1, characterized in that: The plurality of protrusions (111) are distributed at intervals, and the positive electrode sheet (100) comprises a straight portion (130) between two adjacent protrusions (111); The distance between the centers of two adjacent convex portions (111) is L1, the length of the straight portion (130) between two adjacent convex portions (111) is L2, and L1 and L2 satisfy the relationship: L1 / L2=1.05~10.

7. The electrode assembly according to claim 6, characterized in that: L1 = 3 mm to 10 mm; And / or, L2=0.5mm~8mm.

8. The electrode assembly according to claim 1, characterized in that: The area of ​​the convex portion (111) is Q1, and the area of ​​the concave portion (121) is Q2. Q1 and Q2 satisfy the relationship: Q1 / Q2=1.02~1.21; And / or, the projection area of ​​the convex portion (111) in the thickness direction of the positive electrode sheet (100) is S1, and the projection area of ​​the concave portion (121) in the thickness direction of the positive electrode sheet (100) is S2, and S1 and S2 satisfy the relationship: S1 / S2=1.02~1.

21.

9. The electrode assembly according to claim 1, characterized in that: The number of the protrusions (111) within a unit area of ​​the positive electrode sheet (100) is N, and N satisfies the relationship: 2≤N≤25, and / or the total projected area of ​​each of the protrusions (111) within the unit area in the thickness direction of the positive electrode sheet (100) is S3, and the proportion of S3 within the unit area satisfies the relationship: 0.2≤S3≤0.8。 10. The electrode assembly according to any one of claims 1 to 9, characterized in that: The area on the positive electrode sheet (100) where the convex portions (111) are centrally arranged is a convex portion area (140), the total area of ​​the convex portion area (140) is S11, the total area of ​​the positive electrode sheet (100) is S, and S11 and S satisfy the relationship: 0.02≤S11 / S≤0.

85.

11. The electrode assembly according to claim 10, characterized in that: The distance between the convex region (140) and the two end edges of the positive electrode sheet (100) in the length direction is K, wherein K=10 mm to 100 mm; and / or The distance between the convex region (140) and any end edge of the positive electrode sheet (100) in the width direction is M, where M=5 mm to 30 mm.

12. The electrode assembly according to any one of claims 1 to 9, characterized in that: The positive electrode sheet (100), the separator (200) and the negative electrode sheet (500) are stacked and wound to form a winding core structure, and the electrode assembly includes a main body area (300) and an arc area (400); the height of the protrusion (111) located in the arc area (400) is smaller than the height of the protrusion (111) located in the main body area (300).

13. The electrode assembly according to any one of claims 1 to 9, characterized in that: The diaphragm (200) comprises: A base film, the base film comprising a multi-layer microporous film; A ceramic layer is coated on the base film, and the ceramic layer and the positive electrode sheet (100) are arranged opposite to each other.

14. The electrode assembly according to claim 13, characterized in that: The metal element content of the first surface (110) is W1, and the metal element content of the second surface (120) is W2, and W1 and W2 satisfy the relationship: W1>W2; The metal element includes at least one of Al, Si, Ce, Mg, Zr or Ti.

15. The electrode assembly according to claim 13, characterized in that: The metal element content of the convex portion (111) is W11, and the metal element content of the concave portion (121) is W21. The W11 and W21 satisfy the relationship: W11>W21; and / or The positive electrode sheet (100) comprises a straight portion (130) between two adjacent convex portions (111); The metal element content of the convex portion (111) is W11, and the metal element content of the straight portion (130) is W3. W11 and W3 satisfy the relationship: W11>W3; and / or The positive electrode sheet (100) comprises a straight portion (130) between two adjacent convex portions (111); The metal element content of the straight portion (130) is W3, and the metal element content of the concave portion (121) is W21. W211 and W3 satisfy the relationship: W3>W21; The metal element includes at least one of Al, Si, Ce, Mg, Zr or Ti.

16. The electrode assembly according to any one of claims 1 to 9, characterized in that: The tensile strength of the positive electrode sheet (100) is ≥100 MPa, and the ratio of the depth of the recess (121) to the tensile strength (MPa) of the positive electrode sheet (100) is between 0.05 and 0.

2.

17. The electrode assembly according to claim 13, characterized in that: The ceramic layer is an inorganic ceramic particle coating, a coating of inorganic ceramic particles and PVDF composite, or a coating of inorganic ceramic particles and polymethyl methacrylate and PVDF composite; wherein, The inorganic ceramic particles include one or more of α-Al2O3, γ-Al2O3, Al2O3, SiO2, CeO2, MgAl2O4, ZrO, and TiO2; The polymethyl methacrylate is in the form of block-shaped or strip-shaped convex structures.

18. The electrode assembly according to claim 1, characterized in that The negative electrode sheet (500) comprises a negative electrode current collector and a negative electrode active material layer, wherein the negative electrode active material layer comprises a silicon-carbon composite material and / or a silicon-oxygen composite material.

Citation Information

Patent Citations

  • Battery

    CN116315142A

  • Secondary battery and separator for secondary battery

    CN116613469A

  • Electrode piece, electrode assembly and battery

    CN117637991A

  • Pole piece, roller piece, electrode assembly, battery monomer, battery and electric device

    CN218548477U

Cited By

  • Electrode assembly

    WO2026113805A1